2023
DOI: 10.1007/s10654-022-00961-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and risk of chronic kidney disease: systematic review and meta-analysis of 12 cohort studies involving 1,281,727 participants

Abstract: The role of regular physical activity in preventing vascular and non-vascular disease is well established. Chronic kidney disease (CKD) is a major cause of global morbidity and mortality and largely preventable, but it is uncertain if regular physical activity can reduce the risk of CKD. Using a systematic review and meta-analysis of published observational cohort studies in the general population, we sought to assess the association between physical activity and CKD risk. Relevant studies with at least one-ye… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 78 publications
(110 reference statements)
0
6
0
Order By: Relevance
“…It is shown that short sleep time and poor sleep quality may have a direct effect on CKD through the renin-angiotensin-aldosterone system and sympathetic nervous system activation (19)(20)(21). Additionally, low physical activity and prolonged sedentary time may increase the risk of CKD by increasing insulin and vascular resistance (22)(23)(24). Moreover, longer working hours are strongly linked with increased psychosocial stress among employees (25), and higher levels of psychosocial distress with a faster decline in kidney function (26).…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that short sleep time and poor sleep quality may have a direct effect on CKD through the renin-angiotensin-aldosterone system and sympathetic nervous system activation (19)(20)(21). Additionally, low physical activity and prolonged sedentary time may increase the risk of CKD by increasing insulin and vascular resistance (22)(23)(24). Moreover, longer working hours are strongly linked with increased psychosocial stress among employees (25), and higher levels of psychosocial distress with a faster decline in kidney function (26).…”
Section: Discussionmentioning
confidence: 99%
“…A healthy lifestyle is an important way to improve the quality of life and prevent various chronic diseases, including CKD. Although lifestyle behaviours, such as physical activity, speci c dietary patterns, and smoking, are known to be associated with the development of CKD [20][21][22], the in uence of alcohol intake on the risk of developing CKD is inconsistent in the general population [5][6][7][8][9][10][11][12][13][14]. Furthermore, only two studies have investigated the association between alcohol consumption and renal function decline in older adults [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) characterized by proteinuria and low glomerular filtration rate (GFR) [ 1 ] is a major global health problem [ 2 ] and an enormous economic burden [ 3 ], because patients with CKD are at higher risk of end-stage kidney disease (ESKD) [ 4 ], cardiovascular disease (CVD) [ 5 , 6 ], and all-cause mortality [ 6 ]. Multiple studies have identified modifiable lifestyle factors as risk factors for incidence of CKD, including smoking [ 7 ], physical inactivity [ 8 , 9 ], sedentary behavior [ 10 ], short sleep duration [ 11 , 12 ], and unhealthy dietary behaviors, including poor dietary patterns [ 13 ], breakfast skipping [ 14 ], and low vegetable consumption [ 15 , 16 ]. To establish an effective CKD prevention strategy, the association between the modifiable lifestyle factors and CKD should be clarified extensively.…”
Section: Introductionmentioning
confidence: 99%